Literasi Keuangan Keluarga: Panduan Praktis Perlindungan Hukum Investasi dalam Menjaga Kesehatan Keluarga - Fadzlurrahman Fadzlurrahman; Tali Tulab (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Family health is influenced not only by physical conditions but also by mental and social factors, including the economic situation of the family. The rapid development of financial technology, particularly online lending, provides easier access to financial services but also poses risks to the community, especially related to economic pressure and family mental health. This community service activity aimed to improve public knowledge and awareness of family health through financial literacy education and online loan prevention. The activity was conducted in Tamansari Village, Mranggen District, Demak Regency, using counseling sessions, discussions, and evaluation through pre-test and post-test methods. The results showed a significant increase in community knowledge across all indicators, including understanding the impact of online loans on family mental health, which increased from 40% to 90%, and awareness of the importance of communication and financial transparency within families, which increased from 50% to 93%. This activity generated positive social impacts, such as increased collective awareness, more cautious financial decision-making, and strengthened family roles in maintaining health. Therefore, financial literacy education can serve as an effective promotive and preventive strategy for improving family health in the community